Os gêneros narrativos e as temáticas sociais em ficções seriadas brasileiras para streaming - Simone Maria Rocha; Marcos Vinicius Meigre e Silva (Les Cahiers ALHIM)
Driven by the arrival of global online television portals, the production of serialized fiction in Brazil has diversified in industrial, narrative and cultural terms, linked to the global audiovisual scene. In light of this, the aim of this article is to explore, through a cultural analysis, the industrial macro-contextualization of the platforms that produce original serial fiction, in order to identify narrative genres and predominant social themes. We observed that there is a geographical concentration of production companies associated with streaming services and, in addition, the classification of drama as the main genre of the works generated a variation of subgenres, in an effort by the local industry to align itself with the parameters of global productions. Finally, the thematic approaches avoid reductionist treatments and promote reflections aimed at building more pluralistic, democratic and citizen-based societies.